Coaxial Microdispensing of ZnO/PVDF and Graphite/PVDF Composite Using 3D Printed Spinneret for Fabrication of Crossbar Array Photodetector - Bisht, Bhanu Prakash; Toutam, Vijaykumar; Dhakate, Sanjay R.; Khan, Mohd Aamir; Basheed, Gounda Abdul (ACS applied engineering materials, 2025)
A coaxial wire crossbar array photodetector using the microdispensing technique is demonstrated in the present work. Graphite/PVDF-ZnO/PVDF (core–shell) coaxial photodetectors are fabricated using a custom-designed DLP 3D-printed coaxial spinneret. The rheological study of the composites showed that ZnO/PVDF with 80/20 wt % (C2) and graphite/PVDF with 90/10 wt % (E1) exhibit optimal viscosities of 50E6 and 70E7 cP, respectively. C2 composite shows both storage and loss moduli of ∼500 Pa. Similarly, the E1 composite shows both storage and loss moduli of ∼1400 Pa. Also, C2 and E1 show quick retention of shape during microdispensing, with estimated relaxation times of 47.1 and 78.5 ms for C2 and E1, respectively. Raman spectroscopy displays signature peaks of ZnO, graphite, and PVDF. The UV–vis absorbance data show absorbance at 370 nm UV and a band gap of ∼3.2 eV for the ZnO/PVDF composite. Coaxial wires with different diameters are dispensed by varying the extrusion pressure from 50 to 160 kPa for the core while maintaining a constant extrusion pressure of ∼50 kPa for the shell, and the corresponding photodetectors exhibit a direct correlation between photoconductivity and shell thickness. Of all the photodetectors, DL shows better enhancement of ∼1.2 μA, high responsivity of ∼1.7 × 10–4 A/mW, and on/off ratio of ∼120, with a fast response time of 27/18 ms for both rise and decay. All of the devices show long-term stability of the photocurrent. The intensity-dependent photocurrent of all the devices is studied by power law fitting, and the nonlinear constant (θ) is estimated to be θ ≈ 0.90 for device DL, whereas DM and DS show θ ≈ 0.76 and 0.66, respectively. Also, the feasibility of fabricating a crossbar array photodetector is demonstrated, and the effect of the ITO electrode width on the enhancement and responsivity is studied.